ПОВЫШЕНИЕ ЭФФЕКТИВНОСТИ КОНТУРНОГО ЭКРАНИРОВАНИЯ МАГНИТНОГО ПОЛЯ ВЫСОКОВОЛЬТНЫХ КАБЕЛЬНЫХ ЛИНИЙ - Розов, В.Ю.; Добродеев, П.Н.; Ерисов, А.В.; Ткаченко, А.О. (Інститут електродинаміки НАН України, Київ, 2016)
Proposed a method for increasing the efficiency of the screening of the magnetic field of cable lines in the area of twopoint bonding of single-core cable screens, based on an increase of inductance of the closed screen circuits by using of additional ferromagnetic cores covering the cables. Presented results of theoretical and experimental studies, confirming the 2-4-fold increase in shielding effectiveness using the method. The recommendations on the choice of the value of the inductance introduced depending on the desired rate of screening, cable parameters and the length of the shielded area. References 5, figures 5.